2003
DOI: 10.1128/mcb.23.11.3798-3812.2003
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin and Its Family Members Can Promote the Cell-Free Deadenylation of AU-Rich Element-Containing mRNAs by Poly(A) Ribonuclease

Abstract: Eukaryotic mRNA stability can be influenced by AU-rich elements (AREs) within mRNA primary sequences. Tristetraprolin (TTP) is a CCCH tandem zinc finger protein that binds to ARE-containing transcripts and destabilizes them, apparently by first promoting the removal of their poly(A) tails. We developed a cell-free system in which TTP and its related proteins stimulated the deadenylation of ARE-containing, polyadenylated transcripts. Transcript deadenylation was not stimulated when a mutant TTP protein was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
221
2
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(234 citation statements)
references
References 39 publications
6
221
2
5
Order By: Relevance
“…The formation of a large oligomer of TTP was also supported by GMSA, in which active TTP-ARE complexes were found in the wells of the autoradiograph at high TTP concentrations. Immunoblotting showed that some TTP was in a size of dimer even under SDS denaturation ( Figure 5), in a manner similar to those following cross-linking with disuccinimidyl suberate (42) and the E. coli glycerol facilitator on SDS-PAGE (43). The major form of active TTP from transfected mammalian cells being a tetramer is in agreement with previous results using the MBP-hTTP fusion protein purified from overexpressed E. coli cells (9).…”
Section: Discussionsupporting
confidence: 90%
“…The formation of a large oligomer of TTP was also supported by GMSA, in which active TTP-ARE complexes were found in the wells of the autoradiograph at high TTP concentrations. Immunoblotting showed that some TTP was in a size of dimer even under SDS denaturation ( Figure 5), in a manner similar to those following cross-linking with disuccinimidyl suberate (42) and the E. coli glycerol facilitator on SDS-PAGE (43). The major form of active TTP from transfected mammalian cells being a tetramer is in agreement with previous results using the MBP-hTTP fusion protein purified from overexpressed E. coli cells (9).…”
Section: Discussionsupporting
confidence: 90%
“…Immunodepletion of the Xenopus orthologue of HuR from oocyte extracts had no effect on the ARE-directed deadenylation of an exogenous RNA in vitro (46). Recently, TTP has been shown to promote ARE-directed deadenylation in a cell-free system (29). However, in cells lacking TTP, such as the HeLa cells used in this study, it is unknown which factor is responsible for targeting ARE-containing mRNAs for rapid deadenylation or for inhibition of deadenylation by p38 MAPK.…”
Section: P38 Mapk Inhibits Are-directed Deadenylationmentioning
confidence: 46%
“…Despite the identification of numerous ARE-binding proteins (ARE-BPs), it is unclear which (if any) provides a link between p38 MAPK and the ARE. One ARE-BP, tristetraprolin (TTP), is destabilizing and directs deadenylation (29). It is an in vitro substrate of MAPKAPK-2 (30); however, TTP is not necessarily involved in the basic stabilization mechanism because it is not expressed in HeLa cells in which regulation of reporter mRNAs by p38 MAPK has been studied.…”
mentioning
confidence: 99%
“…TIS11b belongs to a family of RNA-binding proteins (comprising also TIS11/TTP/tristetraprolin and TIS11d) that share characteristic tandem CCCH-type zinc-finger domains. The canonical family member, TTP, has been shown to bind to AREs in the 3 0 -UTR of tumour necrosis factor a (TNFa) mRNA through these zinc-finger domains, and to decrease TNFa mRNA stability by promoting its deadenylation and degradation (Carballo et al, 1998;Lai et al, 2003). All members of the family are involved in regulation of several short-lived cytokine mRNAs including granulocyte macrophage colony-stimulating factor (GM-CSF), and interleukin 3 (Carballo et al, 2000;Stoecklin et al, 2000) and appear to share similar ARE-binding and mRNA-destabilizing activities.…”
Section: Introductionmentioning
confidence: 99%